Ludic Scopes for Environmental Crisis and Education. Issue 2 (1st June 2019) - Osti, Giorgio
Abstract : The article aims to add a ludic perspective to those generally used for studying environmental issues in social sciences. To introduce in the debate a play/game metaphor enriches the interpretations of environmental crisis and provides a further motivation to action. The ludic perspective has a sociorelational background. That tradition of studies helps in constructing a set of categories that are then applied to environmental education (EE). The choice of such a topic is motivated by two factors: EE is an aspect generally practiced but mistreated in the main theorizations, and EE is exemplary of the potentialities of the playing games metaphor, which are the desire to create, the acceptance of slow changes, the protection of an experimental bubble, and irony toward environmental issues.